Fine-Needle Aspiration Biopsy and Endoscopic Ultrasound for Pretreatment Pathological Diagnosis of Gastric Gastrointestinal Stromal Tumors. (26th September 2012) - Ito, Hiroaki; Inoue, Haruhiro; Ryozawa, Shomei; Ikeda, Haruo; Odaka, Noriko; Eleftheriadis, Nikolas; Maselli, Roberta; Sando, Norimasa; Kimura, Satoshi; Kudo, Shin-ei
Abstract : Background . Although it is possible to visualize gastrointestinal stromal tumors (GIST) of the stomach by endoscopy, their pretreatment histological diagnosis is often difficult. The aim of this study was to investigate predictors of accurate preoperative pathological diagnosis of gastric GIST. Material and Methods . We retrospectively studied patients with gastric GIST who had undergone pretreatment endoscopic biopsy and surgery, and examined their clinicopathological data. Results . Twenty-three patients were eligible. Thirty-four endoscopic biopsies (mean 2.6, range 1–8) were obtained. Preoperative pathological diagnoses of GIST were made in 18 patients. Precise diagnoses were made in 18 (52.9%) of the 34 biopsies. Endoscopic ultrasound (EUS) resulted in precise diagnoses in 11 (91.7%) of the 12 biopsy specimens. Fine-needle aspiration (FNA) biopsy resulted in precise diagnoses in 11 (84.6%) of the 13 biopsy specimens. The accuracy of pathological diagnosis by EUS-guided FNA biopsy was 100%. The procedure of EUS-guided FNA biopsy had no complications or recurrent disease. In a multivariate analysis, only EUS achieved a significantly superior rate of diagnosis (odds ratio, 11.884; 95% confidence interval, 1.204–289.230; P = 0.034 ). Conclusion . EUS-guided FNA biopsy is the most accurate for pretreatment pathological diagnosis of gastric GIST and for prevention of both of early complications and disease recurrence.